Effects of trap density on drain current LFN and its model development for E-mode GaN MOS-HEMT. (December 2017) - Panda, D.K.; Lenka, T.R.
Abstract: In this paper the drain current low-frequency noise (LFN) of E-mode GaN MOS-HEMT is investigated for different gate insulators such as SiO2, Al2 O3 /Ga2 O3 /GdO3, HfO2 /SiO2, La2 O3 /SiO2 and HfO2 with different trap densities by IFM based TCAD simulation. In order to analyze this an analytical model of drain current low frequency noise is developed. The model is developed by considering 2DEG carrier fluctuations, mobility fluctuations and the effects of 2DEG charge carrier fluctuations on the mobility. In the study of different gate insulators it is observed that carrier fluctuation is the dominant low frequency noise source and the non-uniform exponential distribution is critical to explain LFN behavior, so the analytical model is developed by considering uniform distribution of trap density. The model is validated with available experimental data from literature. The effect of total number of traps and gate length scaling on this low frequency noise due to different gate dielectrics is also investigated. Highlights: Flicker noise simulation of GaN MOS-HEMT by impedance field method. Effects of different gate dielectrics on flicker noise PSD is investigated. An analytical drain current flicker noise model is developed. The model is in good agreement with available experimental data from literature. The effect of traps distribution and gate length scaling on flicker noise is investigated.